A simple approach to the evaluation of the actual water renewal time of natural stratified lakes. Issue 4 (1st April 2014) - Pilotti, Marco; Simoncelli, Stefano; Valerio, Giulia
Abstract In natural lakes, where thermal stratification hinders complete mixing, the theoretical value T0 of the water renewal time provides a low‐order approximation to the time T37 when 37% of the original water is still present within the lake; this time could be operatively regarded as the actual value of the water renewal time. In this paper, we present a simple nonparametric model to estimate the age distribution of water within stratified natural lakes, taking into account fundamental aspects of its mass exchange and thermal evolution. This distribution provides a straightforward way to compute T37. The model is presented as a system of ordinary differential equations along with a MATLAB script for its numerical solution, so that it can be easily applied to lakes where a minimum of limnological data are available, without the need of extensive meteorological data set and modeling expertise that an hydrodynamic model would require to the same purpose. The case of a deep oligomictic Italian prealpine lake (Lake Iseo) is considered: after a positive comparison with the results obtained using a 1‐D lake hydrodynamic model, the reiterated application to the available time series allows to approximate the water age probability distribution. This distribution is used to compute the actual value of the water renewal time, that resulted T37 = 1.6T0.